Between figuration and abstraction: Contemporary Christian art - Cuesta Gómez, Daniel (Razón y fe, 2022)
After centuries in which art was fundamentally religious and mostly Christian, the rupture of the modern artistic world with the Church, together with the abandonment of the classical canons, plunged religious art into a serious intellectual and material crisis. This leads us to ask the question about the possibility of a contemporary Christian art that can speak to the men of today and lead them to God from the aesthetic experience, or if, on the contrary, it is necessary to opt for a continuist art with the past epochs that, nevertheless, can connect with the contemporary restlessness.
Keywords: Contemporary Christian art; abstraction; figuration; aesthetic experience; incarnation